Jews and Muslims in London and Amsterdam Conflict and Cooperation, 1990-2020 - Vellenga, Sipco J. (Routledge Studies in Religion, 2023)
This book focuses on the development of bilateral Jewish-Muslim relations in London and Amsterdam since the late-1980s. It offers a comparative analysis that considers both similarities and differences, drawing on historical, social scientific, and religious studies perspectives. The authors address how Jewish-Muslim relations are related to the historical and contemporary context in which they are embedded, the social identity strategies Jews and Muslims and their institutions employ, and their perceived mutual positions in terms of identity and power. The first section reflects on the history and current profile of Jewish and Muslim communities in London and Amsterdam and the development of relations between Jews andMuslims in both cities. The second section engages with sources of conflict and cooperation. Four specific areas that cause tension are explored: the Israeli-Palestinian conflict; antisemitism and Islamophobia; attacks by extremists; and the commemoration of wars and genocides. In addition to 'trigger events', what stands out is the influence of historical factors, public opinion, the 'mainstream' Christian churches and the media, along with the role of government. The volume will be of interest to scholars from fields including religious studies, interfaith studies, Jewish studies, Islamic studies, urban studies, European studies, and social sciences as well as members of the communities concerned, other religious communities, journalists, politicians, and teachers who are interested in Jewish-Muslim relations.